The Pink Tax in Consumer Behavior for Personal Care Products - Pramesti, Adenia Naura (Journal of Consumer Studies and Applied Marketing, 2024)
Pricing significantly influences consumer decisions, with variations often observed for similar products due to purchase timing, market segments, and Gender. This phenomenon, known as price discrimination, can raise ethical concerns, especially when it exacerbates inequalities. A notable example is the "pink tax," where products marketed towards women are priced higher. Despite legislative efforts like California's Gender Tax Repeal Act and similar measures in New York, gender-based pricing disparities persist, particularly in personal care products. This study explores consumer perceptions of pricing fairness in personal care products and the impact of the pink tax on purchasing decisions. The research employs a mixed-methods approach, combining surveys to gather quantitative data and semi-structured interviews for qualitative insights. The surveys measure public awareness and attitudes towards the pink tax, while in-depth interviews with women who frequently purchase personal care products provide an understanding of their experiences. The results are expected to reveal that consumers generally perceive the pink tax as unfair and exploitative, influencing their purchasing behaviour and attitudes towards gender-neutral products. This study will contribute to understanding gender-based pricing and its effects on consumer behaviour in Indonesia, offering insights for promoting fairer pricing practices.